Aborted stock repurchases and earnings quality. Issue 9 (2nd September 2014) - Sun, Qian; Yung, Kenneth; Rahman, Hamid
Abstract : Purpose: – The purpose of this paper is to try to identify the motivation of firms that announce share repurchase but do not follow it up with the actual purchase. The authors conjecture that the long-term earnings quality of such firms is low, which makes them poor candidates for actual stock repurchase. Their intention is to mimic actual repurchasers and their motivation appears to be just to get a bounce in their stock price normally associated with such announcements. Design/methodology/approach: – The authors use probit analysis to ascertain whether earnings quality can predict the subsequent repurchase behavior of firms that announce share repurchase. As Gong et al. point out, the relationship between earnings management and the percentage of shares repurchased may be endogenous. In order to mitigate the potential endogeneity bias, the authors use a two-stage instrumental variable probit model adapted for this study from Lee and Masulis (2009). Findings: – The results show that non-carry-through firms have lower earnings quality than carry-through firms in the pre-announcement period in all of the metrics the authors use to measure earnings quality. In the post-announcement period, the earnings quality of the non-carry-through firms declines still further and the difference in the quality becomes more pronounced. The results of probit regression show that lower earnings quality increases the likelihood of becoming a non-carry-through company. Research limitations/implications: – The finding has interesting implications for investment management as investors can differentiate non-carry-through firms from carry-through repurchasers by examining the firm's earnings quality. Originality/value: – The analysis shows that poor long-term earnings quality increases the chance of not carrying through on the repurchase announcement. The authors also find that the poor earnings quality of non-carry-through firms limits their ability to manage earnings downward prior to the repurchase announcement.